The news among youngsters: a journalistic literacy project - Bonacho, Fernanda (2018)
The main objective of this poster is to present the first findings of the project TJAME – Transliteracia Jornalística: até que o mundo fique tal como é (Journalitic Transliteracy: until the world becomes itself). Developed between March and May of 2018, the pilot experience was part of a new journalistic literacy research plan hosted at ESCS/Lisbon Polytechnic Institute. Counting with researchers and professionals with a solid experience in the field of journalism and communication sciences, TJAME focused on journalistic literacy among youngsters finishing their high school and journalism undergraduate studies. The working period included a wide range of immersive journalistic practices for more than 50 students from the area of Lisbon. The poster will tell the story of this literacy project, standing out the facts and numbers of the experience, the differences between participants' expectations and practices, wishing to trigger a different journalistic literacy debate based on clear awareness.